2014
DOI: 10.2480/agrmet.d-14-00006
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between diurnal patterns of root respiration and leaf photosynthesis in Quercus crispula and Fagus crenata seedlings

Abstract: The physiological traits of tree roots have been considered associating with photosynthetic capacity; however, the linkages between diurnal patterns of root respiration and assimilation in individual leaves are poorly understood. Our objectives were to investigate the diurnal patterns of tree root respiration and the assimilation under natural luminous environments and to explore the potential environmental drivers of root respiration and the assimilation by relating trees' diurnal cycle to commonly measured v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…In September and October, R s relative to the soil temperature was higher in the morning than at night. Diurnal hysteresis in the relationship between R s and soil temperature is an example of multiple processes interacting to produce highly variable photosynthetic attributes [ 30 , 31 ]. Liu et al [ 17 ] showed that the diurnal cycle of R s in a mixed deciduous forest was related more to differences in photosynthetically active radiation than to variations in soil environmental conditions, suggesting that diurnal R s patterns were associated with photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In September and October, R s relative to the soil temperature was higher in the morning than at night. Diurnal hysteresis in the relationship between R s and soil temperature is an example of multiple processes interacting to produce highly variable photosynthetic attributes [ 30 , 31 ]. Liu et al [ 17 ] showed that the diurnal cycle of R s in a mixed deciduous forest was related more to differences in photosynthetically active radiation than to variations in soil environmental conditions, suggesting that diurnal R s patterns were associated with photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Photoinhibitory damage and stomatal closure contribute significantly to midday photosynthetic depression and, indirectly, to the decline in C supply to the root system. Makita et al [ 31 ] showed that weather conditions under high temperature stress cause a midday depression of CO 2 assimilation in deciduous trees and then a sharp reduction in autotrophic respiration rate. The flux of new photosynthate to the rhizosphere significantly accelerates microbial activity there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory processes of plant roots and mycorrhizal microorganisms, roughly half of the total soil respiration (Högberg et al, 2009), are highly dependent on recent photosynthates (Högberg et al, 2001). These activities are characterized by large seasonal fluctuations typically due to temperature, moisture and light shifts (Davidson et al, 1998;Luo and Zhou, 2006;Makita et al, 2014). Respiration by plant roots and mycorrhizal symbionts is considered to be more sensitive to changes in temperature, compared to respiration by soil without roots (Boone et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Photoinhibitory damage and stomatal closure contribute signi cantly to photosynthetic depression and indirectly to the decline in C supply to the root system. Makita et al (2014) showed that weather conditions under high temperature stress cause a depression in CO 2 assimilation in deciduous trees and then a sharp reduction in root respiration rate. Indeed, it seems that the PAI and GR ratio in our study slightly decreased from August (Fig.…”
Section: Discussionmentioning
confidence: 99%